1990
DOI: 10.1002/art.1780330702
|View full text |Cite
|
Sign up to set email alerts
|

Association of l‐tryptophan and an illness resembling eosinophilic fasciitis: clinical and histopathologic findings in four patients with eosinophilia‐myalgia syndrome

Abstract: The Centers for Disease Control has recently reported an association between the use of oral Ltryptophan preparations and a disease marked by severe myalgia, peripheral eosinophilia, and neuromuscular and cutaneous abnormalities. They have labeled the condition eosinophilia-myalgia syndrome. We report here the clinical and histopathologic findings in 4 patients who developed an illness resembling eosinophilic fasciitis following the initiation of oral L-tryptophan supplementation.L-tryptophan has gained popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…In the of 206±62 to 110±24 and 131±35 nM after 3 and 6 d current study, we demonstrate that significant dermal and subrespectively (P < 0.001 compared with saline concutaneous inflammation and fibrosis occur when female uinolinic acid returned toward baseline by 2 wk of C57BL/6 mice are administered synthetic EBT by intraperitoosure (180±55 nM; P = NS compared with saline neal injection. EBT appears to be capable ofinducing lesions of and continued to rise to levels that were significantly the dermis and subcutis, including the fascia and perimysium, compared with baseline or saline-treated control ani-consistent with those seen in patients with EMS (2,3,7,8,11). …”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…In the of 206±62 to 110±24 and 131±35 nM after 3 and 6 d current study, we demonstrate that significant dermal and subrespectively (P < 0.001 compared with saline concutaneous inflammation and fibrosis occur when female uinolinic acid returned toward baseline by 2 wk of C57BL/6 mice are administered synthetic EBT by intraperitoosure (180±55 nM; P = NS compared with saline neal injection. EBT appears to be capable ofinducing lesions of and continued to rise to levels that were significantly the dermis and subcutis, including the fascia and perimysium, compared with baseline or saline-treated control ani-consistent with those seen in patients with EMS (2,3,7,8,11). …”
Section: Methodsmentioning
confidence: 54%
“…In addition to eosinophilia and myalgia, many EMS patients developed scleroderma-like skin changes frequently accompanied by fasciitis (2,3,7,8), peripheral neuropathy (9-I 1 ), and pneumonitis ( 12). Remarkably similar clinical and histological changes were observed in patients affected by the toxic oil syndrome (TOS) that occurred in Spain in 1981 (13).…”
Section: Introductionmentioning
confidence: 99%
“…Another histochemical study showed that the acid mucopolysaccharide deposits in EMS patients were almost exclusively made of HA 42 . Biopsies from EMS did not show myonecrosis or vessel destruction, and creatinine kinase levels were also normal 39,41 . Taken together, these findings suggest that the severe myalgia associated with EMS was not due to tissue necrosis but could potentially be caused by ischemia associated with the accumulation of HA.…”
Section: Hyaluronan and Painmentioning
confidence: 86%
“… 38 Although the pathogenesis of this disease is still poorly understood, cutaneous and muscle biopsies of patients with EMS showed accumulation of acid mucopolysaccharide deposits in the fascial and perimysial regions, specifically around the arterioles and small arteries, without evidence of arteritis. 39 , 40 Perineural fibrosis and loss of microvasculature were noted on histopathological studies of EMS patients. 39 Focal perifascicular atrophy was also reported in the progression of the disease.…”
Section: Hyaluronan and Painmentioning
confidence: 99%
“…demic of low vitamin D levels does not cause increased levels of skeletal fragility and unexplained fractures. The diagnosis of EMS also appears to have been originally suggested as the result of an abduction, as researchers tried to make sense of a number of patients who presented with strange and unexplained symptoms (Bulpitt et al 1990;Hertzman et al 1990). Research into the historical processes by which these patterns were identified may be useful in contemporary conversations about how to diagnose disease.…”
Section: Meno's Paradoxmentioning
confidence: 99%